Physical activity coaching by Australian Exercise Physiologists is cost effective for patients referred from general practice. (22nd November 2017) - Ewald, Ben; Stacey, Fiona; Johnson, Natalie; Plotnikoff, Ronald C.; Holliday, Elizabeth; Brown, Wendy; James, Erica L.
Abstract: Objective : Interventions to promote physical activity for sedentary patients seen in general practice may be a way to reduce the burden of chronic disease. Coaching by an exercise physiologist is publicly funded in Australia, but cost effectiveness has not been documented. Methods : In a three‐arm randomised controlled trial, face‐to‐face coaching and telephone coaching over 12 weeks were compared with a control group using the outcome of step count for one week at baseline, three months and twelve months. Program costs and time‐based costs were considered. Quality of life was measured as a secondary outcome. Results : At 12 months, the intervention groups were more active than controls by 1, 002 steps per day (95%CI 244, 1, 759). This was achieved at a cost of AUD$245 per person. There was no change in reported quality of life or utility values. Conclusion : Coaching achieved a modest increase in activity equivalent to 10 minutes walking per day, at a cost of AUD$245 per person. Face‐to‐face and telephone counselling were both effective. Implication for public health : Persistence of increases nine months after the end of coaching suggests it creates long‐term change and is a good value health intervention.